2016
DOI: 10.1177/0192623316664590
|View full text |Cite
|
Sign up to set email alerts
|

MEK and ERK Kinase Inhibitors Increase Circulating Ceruloplasmin and Cause Green Serum in Rats

Abstract: Inhibition of the mitogen-activated protein kinase/extracellular signal-regulated (MAPK/ERK) pathway is an attractive therapeutic approach for human cancer therapy. In the course of evaluating structurally distinct small molecule inhibitors that target mitogen-activated protein kinase kinase (MEK) and ERK kinases in this pathway, we observed an unusual, dose-related increase in the incidence of green serum in preclinical safety studies in rats. Having ruled out changes in bilirubin metabolism, we demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Thus, it is still unclear how maternal diabetes leads to the decreased phosphorylation of Foxo1 in the liver of STZ male offspring. Because additional factors that regulate the localisation and activity of Foxo1 were identified recently 35,42,43 , further studies of all regulatory factors, including the newly identified regulatory factors, are needed to clarify the molecular mechanism underlying the decreased phosphorylation and increased activity of Foxo1.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is still unclear how maternal diabetes leads to the decreased phosphorylation of Foxo1 in the liver of STZ male offspring. Because additional factors that regulate the localisation and activity of Foxo1 were identified recently 35,42,43 , further studies of all regulatory factors, including the newly identified regulatory factors, are needed to clarify the molecular mechanism underlying the decreased phosphorylation and increased activity of Foxo1.…”
Section: Discussionmentioning
confidence: 99%
“…That ERK cellular pathway is one of the critical signals of FoxO1 phosphorylation. The inhibition of ERK and MEK attenuate phosphorylation resulting in the activation of Foxo1 in rat hepatocytes 61 . Phosphorylation of FoxO1 is invalid in binding to ATG7 for autophagy initiation in mouse ovarian granulosa cells.…”
Section: Foxo1‐meditated Cellular Autophagy Maintains the Homeostasis...mentioning
confidence: 98%
“…The inhibition of ERK and MEK attenuate phosphorylation resulting in the activation of Foxo1 in rat hepatocytes. 61 Phosphorylation of FoxO1 is invalid in binding to ATG7 for autophagy initiation in mouse ovarian granulosa cells. The FSH or melatonin induces both Akt‐mediated phosphorylation and Sirt1‐mediated deacetylation of FoxO1.…”
Section: Foxo1‐meditated Cellular Autophagy Maintains the Homeostasis...mentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution by Carter, Cregar, and Aulbach (2016) provides an updated and comprehensive assessment of normal bone marrow cytology in the nonhuman primate, further expanding the reference literature for nonclinical toxicity studies. Finally, we have a case example of the mechanistic workup and evidence-based risk assessment of an unusual clinical pathology finding—drug-induced green discoloration of the serum (Diaz et al 2016).…”
mentioning
confidence: 99%